A cross sectional study on the determinants of railway fatalities in different age groups - Chatterjee, Arabinda; Das, Rina; Mukherjee, Anindya; Das, Somnath (International Journal of Research in Medical Sciences, 2022)
Background: Over the last few decades many railway accidents and fatalities have occurred in India as well as worldwide. Cities having a high economic activity and are complex spatial structures, are supported by transport systems. The evolution of mass rapid transport system in the form of sub-urban railway network has increased railway casualties in the cities as the railroads pass through residential and commercial zones. Methods: This cross-sectional observational study was conducted at R. G. Kar medical college and hospital police Morgue attached to the department of forensic medicine and toxicology (FMT), Kolkata on the randomly selected medico legal postmortems over last 4 years. Results: Railway accidents were common in males with mean age group of 38.98 years and was almost identical with the female mean age. The accidents mostly occurred in the office hours during the day time. Chi square test of association gave significant results between the different age groups with sex and grievous injuries sustained the people. Injuries sustained by the train showed that they were found mostly over the head followed by spine and thorax. Major cause of death was due to head injuries. Conclusions: The article gives an idea about the relevant demographic profiles and association with the age-related factors that can be taken up as means to prevent the accidents.